Plan de negocios para el desarrollo de una empresa de e-commerce de calzado femenino en la Ciudad de Trujillo. - Asto Sifuentes, Jeisser Augusto (2019)
The current research “Business plan for the creation of a shoes e-businesscompany in the city of Trujillo”, has as its primary objective developing an electronic business model so-called B2C (Business to consumer) with a multibrand presence, only shoes top-brands of Trujillo and considering as our flagship brand “Dimussa”. For the market research, the measuring technique was the poll, considering sample population of 386. We have reached the preliminary conclusion in the evolution of the consumer, in respect of their preferences and taste. Moreover, the market share considered was 20% and it was realized a sales forecast for each of our four shoe lines, which are ballerinas, platforms, sandals and boots. Our main strategies are differentiation of products and leadership in costs. The best quality raw materials and inputs will be used in order to produce a higher quality product in terms of durability and comfort. Nevertheless, our prices will be slightly lower than those of the competition. Another important point are strategic alliances with shoe-making suppliers in order to assure an efficient supply of products, as well as to achieve the best pricing and delivering conditions. Therefore, offer the best product at the best price. Vis-à-vis the public, the e-business will have an appealing web shop developed with the highest standards of user experience design and user interface design. Thus, putting clients at center of the shopping experience. The total investment for the project will amount to 102,799.49 S/. which will be financed by shareholders and a bank entity. To sum up, the project is profitable according to the following economic indicators such as VAN: S/. 165, 613 and TIR: 65%.